Hubungan Keterampilan Mengajar Guru dengan Hasil Belajar IPS Murid UPT SD Negeri 1 Centre Pattallassang Kabupaten Takalar - Nurfadilah Dwi Susanty; Muhammad Nawir; Syamsuriyanti Syamsuriyanti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
The formulation of the research problem is, "Is there a relationship between teacher teaching skills and student learning outcomes at UPT SD Negeri 1 Center Pattallassang, Takalar Regency". Thus this study aims to determine the relationship between teacher teaching skills and student learning outcomes at UPT SD Negeri 1 Centere Pattallssang, Takalar Regency.This type of research includes correlational research which aims to determine the relationship between teaching skills and student learning outcomes at UPT SD Negeri 1 Center Pattallssang, Takalar Regency. The sample used was sixth grade UPT SD Negeri 1 Center Pattallssang Takalar Regency as many as 32 students. Given that this population is large, the authors used purposive sampling. In collecting data used are questionnaires and documentation.The results showed that the teaching skills of teachers and student learning outcomes at school had a close and distinct relationship in the very high category, and there was a positive relationship between teacher teaching skills and student learning outcomes at school.